High-resolution epitope mapping of anti-Hu and anti-Yo autoimmunity by programmable phage display. Issue 2 (3rd August 2020) - O'Donovan, Brian; Mandel-Brehm, Caleigh; Vazquez, Sara E; Liu, Jamin; Parent, Audrey V; Anderson, Mark S; Kassimatis, Travis; Zekeridou, Anastasia; Hauser, Stephen L; Pittock, Sean J; Chow, Eric; Wilson, Michael R; et al.
Abstract: Paraneoplastic neurological disorders are immune-mediated diseases understood to manifest as part of a misdirected anti-tumor immune response. Paraneoplastic neurological disorder-associated autoantibodies can assist with diagnosis and enhance our understanding of tumor-associated immune processes. We designed a comprehensive library of 49-amino-acid overlapping peptides spanning the entire human proteome, including all splicing isoforms and computationally predicted coding regions. Using this library, we optimized a phage immunoprecipitation and sequencing protocol with multiple rounds of enrichment to create high-resolution epitope profiles in serum and cerebrospinal fluid (CSF) samples from patients suffering from two common paraneoplastic neurological disorders, the anti-Yo ( n  = 36 patients) and anti-Hu ( n  = 44 patients) syndromes. All (100%) anti-Yo patient samples yielded enrichment of peptides from the canonical anti-Yo (CDR2 and CDR2L) antigens, while 38% of anti-Hu patients enriched peptides deriving from the nELAVL (neuronal embryonic lethal abnormal vision like) family of proteins, the anti-Hu autoantigenic target. Among the anti-Hu patient samples that were positive for nELAVL, we noted a restricted region of immunoreactivity. To achieve single amino acid resolution, we designed a novel deep mutational scanning phage library encoding all possible single-point mutants targeting the reactive nELAVL region. This analysis revealed a distinct preference for the degenerate motif, RLDxLL, shared by ELAVL2, 3 and 4. Lastly, phage immunoprecipitation sequencing identified several known autoantigens in these same patient samples, including peptides deriving from the cancer-associated antigens ZIC and SOX families of transcription factors. Overall, this optimized phage immunoprecipitation sequencing library and protocol yielded the high-resolution epitope mapping of the autoantigens targeted in anti-Yo and anti-Hu encephalitis patients to date. The results presented here further demonstrate the utility and high-resolution capability of phage immunoprecipitation sequencing for both basic science and clinical applications and for better understanding the antigenic targets and triggers of paraneoplastic neurological disorders. Abstract : Phage display and immunoprecipitation sequencing was used to screen the peptide-binding affinities of 80 patients suffering from anti-Hu or anti-Yo paraneoplastic disease. Patient-binding signatures implicate CDR2L as the primary antigen in anti-Yo paraneoplastic disease and suggest that rare exons/isoforms play a role in the anti-Hu oncoimmune response. Graphical Abstract: